2017
DOI: 10.1186/s12958-017-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of in vitro fertilization in women with subclinical hypothyroidism

Abstract: BackgroundPrevious studies examining associations between subclinical hypothyroidism (SCH) with in vitro fertilization (IVF) outcome indicate some benefits of levothyroxine (LT4) treatment. But IVF outcomes in treated SCH women whose serum Thyroid Stimulating Hormone (TSH) concentration did and did not exceed 2.5 mIU/L before the IVF cycle has not been studied thoroughly.MethodsIn this study, we performed a prospective cohort study with 270 treated subclinical hypothyroidism patients undergoing their first IVF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 20 publications
4
31
1
Order By: Relevance
“…However, our updated meta-analysis found no significant improvements in the live birth and clinical pregnancy rates among women receiving LT4 supplementation. This result was consistent with another prospective study that showed no difference in the live birth and clinical pregnancy rates between women with SCH who had TSH levels controlled to < 2.5 mIU/L or 2.5–4.2 mIU/L before IVF [ 20 ]. These negative results suggest that LT4 intervention is a weakly influential factor, as clinical pregnancy and live birth are considered the most important benefits for infertile patients.…”
Section: Discussionsupporting
confidence: 92%
“…However, our updated meta-analysis found no significant improvements in the live birth and clinical pregnancy rates among women receiving LT4 supplementation. This result was consistent with another prospective study that showed no difference in the live birth and clinical pregnancy rates between women with SCH who had TSH levels controlled to < 2.5 mIU/L or 2.5–4.2 mIU/L before IVF [ 20 ]. These negative results suggest that LT4 intervention is a weakly influential factor, as clinical pregnancy and live birth are considered the most important benefits for infertile patients.…”
Section: Discussionsupporting
confidence: 92%
“…Thyroid‐related hormones play significant roles in the various processes of pregnancy, in particular, embryo implantation and maintenance of early pregnancy. Recent reports have shown similar rates of pregnancy and complications during pregnancy in women undergoing IVF with subclinical hypothyroidism during LT4 supplementation compared to those in euthyroid women . In our study, there were also no significant differences in outcomes of assisted reproductive technology in patients with subclinical hypothyroidism, including Hashimoto’s disease, compared to infertile patients with normal TSH levels, but relatively higher clinical pregnancy and lower miscarriage rates were observed, suggesting that LT4 treatment supported successful implantation and prevention of miscarriage.…”
Section: Discussionsupporting
confidence: 58%
“…A stratified analysis by TSH level >4.0 mIU/L did not show any benefit with regard to pregnancy loss between treated and untreated women; importantly, however, note that by study design there were only 17 women with TSH of >4.0 mIU/L. Finally, a large prospective study of 270 patients with SCH undergoing IVF who received LT4 therapy showed similar miscarriage and live birth rate between those who achieved a target TSH level of 0.2 to 2.5 mIU/L compared with a TSH level of 2.5 to 4.2 mIU/L [ 70 ]. These data suggest that there may be no benefit in strictly controlling TSH levels (<2.5 mIU/L) for those women with SCH receiving LT4 therapy who are undergoing assistive reproductive techniques.…”
Section: Treatment Of Schmentioning
confidence: 99%